Methodology for techno–economic optimization of solar assisted heating systems - SHesho, Igor; Tashevski, Done; Mojsovski, Filip (University Politehnica Timisoara, Faculty of Engineering Hunedoara, Romania, 2018)
This paper has objective, to estimate the thermal performance of solar assisted heating systems in regard of solar fraction and perform life cycle cost analysis to assess the feasibility of their implementation in residential sector. In general it is known that the resource for solar thermal systems i.e. the solar irradiation is free, but the equipment to collect it and convert in to useful form (heat or electricity) has a cost. Solar thermal systems are characterized by high investment and low operational cost. It is presented methodology for obtaining the right size of a solar thermal assisted heating system that gives the lowest combination of solar and auxiliary energy costs. Thermal performance of the solar thermal systems are estimated using numerical methods and software since the solar processes are transient in nature been driven by time dependent forcing functions and loads. The system components are defined with mathematical relationships that describe how components function. They are based on first principles (energy balances, mass balances, rate equations and equilibrium relationships) at one extreme or empirical curve fits to operating data from specific machines. As a result of the analysis specific indicators are derived in order to facilitate the techno–economic analysis and design of solar assisted heating systems
Keywords: solar assisted heating systems, thermal performance, specific indicators